2003
DOI: 10.1007/s00467-003-1205-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E therapy in IgA nephropathy: a double-blind, placebo-controlled study

Abstract: IgA nephropathy is the world's most common primary glomerulonephropathy. Recent evidence in a rat model implicated excessive production of oxygen-free radicals in the pathogenesis and suggested that vitamin E-treatment ameliorated progression. We studied this antioxidant therapy on the glomerular filtration rate (GFR), proteinuria and hematuria in biopsy-proven IgA nephropathy in children. The duration of treatment or placebo was 2 years, with vitamin E treatment consisting of 400 IU/day in children weighing <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 23 publications
(29 reference statements)
0
18
0
Order By: Relevance
“…A U-shaped dose response curve may exist for the anti-inflammatory effects of c-TC, with implications for safety (McCary et al 2011). The dose of a-TC in EMP + as recommended (360 IU total from 15 capsules per day) is lower than that shown to be safe and effective in a small RCT in children with immunoglobulin (Ig)A nephropathy (400 or 800 IU/day, respectively for body weights of <30 kg or >30 kg; Chan et al 2003), but significantly more than the United States RDA (http://ods.od.nih.gov/ factsheets/VitaminE-HealthProfessional/ ). Concern about differential responses to vitamin E supplementation in children versus adults and healthy versus chronic disease status exists.…”
Section: Effects On Inflammation and Relation To Mood Changesmentioning
confidence: 99%
“…A U-shaped dose response curve may exist for the anti-inflammatory effects of c-TC, with implications for safety (McCary et al 2011). The dose of a-TC in EMP + as recommended (360 IU total from 15 capsules per day) is lower than that shown to be safe and effective in a small RCT in children with immunoglobulin (Ig)A nephropathy (400 or 800 IU/day, respectively for body weights of <30 kg or >30 kg; Chan et al 2003), but significantly more than the United States RDA (http://ods.od.nih.gov/ factsheets/VitaminE-HealthProfessional/ ). Concern about differential responses to vitamin E supplementation in children versus adults and healthy versus chronic disease status exists.…”
Section: Effects On Inflammation and Relation To Mood Changesmentioning
confidence: 99%
“…Finally, in a randomized, double-blinded study in children with biopsy-proven IgA nephropathy, Chan et al [31] demonstrated that vitamin E significantly reduced proteinuria. While there was a trend to stabilization of glomerular filtration rate in the vitamin E-treated patients, long-term treatment and follow-up are needed to determine whether antioxidant therapy is associated with preservation of renal function.…”
Section: Controlled Clinical Studies In Children With Iga Nephropathymentioning
confidence: 99%
“…Thus proliferation of human mesangial cells and production of immune/chemical mediators and superoxide anions may be amplified by nephritogenic IgA-IC, resulting in kidney lesions commonly seen in IgA nephropathy [26]. The increased production of superoxide anions by kidney mesangial cells [27] and polymorphonuclear leukocytes [26] support a novel direction in the treatment of IgA nephropathy, namely the use of an antioxidant, such as vitamin E, to prevent mesangial cell proliferation and attenuate growth-factor-mediated kidney injury [30, 31]. In parallel with enhanced superoxide production, aggregated IgA induces Fcα receptor expression in leukocytes [27, 32].…”
Section: Pathogenesismentioning
confidence: 99%
“…1 Oxidative damage is thought to be a major mechanism involved in the development of numerous renal disorders including diabetic nephropathy, 2 ischemic nephropathy, 3 some types of iatrogenic nephropathy, 4,5 Balkan endemic nephropathy, 4 IgA nephropathy, 6 and others. 7 As the renal condition worsens and the patient enters chronic renal failure, the resulting uremia leads to systemic oxidative stress and damage to other organs.…”
Section: Introduction Tmentioning
confidence: 99%